Boundedness and Asymptotic Stability for the Solution of Homogeneous Volterra Discrete Equations. (15th February 2018) - Messina, E.; Vecchio, A.
Abstract : We consider homogeneous linear Volterra Discrete Equations and we study the asymptotic behaviour of their solutions under hypothesis on the sign of the coefficients and of the first- and second-order differences. The results are then used to analyse the numerical stability of some classes of Volterra integrodifferential equations.